Development of primary neuronal culture of embryonic rabbit dorsal root ganglia for microfluidic chamber analysis of axon mediated neuronal spread of Bovine Herpesvirus type 1. - Coats, Charles Jason (Kansas State University, 2010)
Bovine herpesvirus type 1 (BHV-1) is an important pathogen of cattle that can cause severe respiratory tract infection known as infectious bovine rhinotracheitis (IBR), abortion in pregnant cows, and is an important component of the Bovine Respiratory Disease Complex (BRDC, “Shipping fever”). The ability of BHV-1 to transport anterogradely from neuron cell bodies in trigeminal ganglia to axon termini in the nasal and ocular epithelia of infected cattle complicates the control of the disease in both vaccinated and infected cattle populations. In calves and rabbits, Us9 deleted viruses have defective anterograde neuronal spread from cell bodies in the trigeminal ganglia to nerve termini in the nose and eye but retrograde spread remains unaffected. To characterize the neuronal spread of BHV-1, we developed primary neuronal cultures using the dorsal root ganglia (DRG) of rabbit embryos. We successfully used microfluidic chamber devices to isolate DRG in the somal compartment and allowed for efficient growth of axons into the axonal compartment. This enabled us to study axon mediated neuronal spread of infection as well as viral transport in axons. Thus, rabbit DRG neuronal culture was susceptible to BHV-1 mutant and wild-type infection, and the method allowed visualization of viral spread in chamber cultures using live cell imaging and fluorescent microscopy. Lastly, using the microfluidic chamber compartmentalized neuron culture system we showed that Us9 acidic domain-deleted and Us9 null mutant BHV-1 viruses had defective anterograde neuronal transport relative to BHV-1 wild type and/or Us9 rescued viruses.
Keywords: Bovine Herpesvirus; Neuronal Transport; Microfluidic Chamber; Biology, Veterinary Science (0778)